(untitled) (KASBIT Business Journal, 2024)
Abstract The study aims to explore the relationship between security perceptions and behavioral inclinations to engage in cybersecurity-related actions in the banking industry of Pakistan. Its rationale is to gain insights into how human factors; specifically perception and attitude affect cybersecurity. The goals of the study are to establish the relation between the perceived risk for cyber threats and security attitudes and explore the effect of perceived benefits on such attitudes and the relation of attitudes to behavioral intentions. Methodology: The research aims at utilizing quantitative research methodology where questionnaires will be utilized as the instrument used to collect information from employee of the banking sector. Hitting the goal of 150 respondents is always a challenge, nonetheless, the sample size is established based on individuals who engage with cybersecurity practices in their workplaces repeatedly. Findings: The study thus provides evidence to support the postulate that PVB, as pertains to security, predict attitude towards security, which determines behavioral intention concerning cybersecurity practices. However, there is the revealed gap between the attitudes and actual actions due to issues to do with the organizational culture and other outside influences that were not mentioned here. Contribution: The research complements the literature on cybersecurity since it focuses on the social aspects of shaping organizational security culture particularly in a developing country. Limitations: Some limitation of the study is that is only confined to banking sector of Pakistan, the findings might not hold good for other sectors in Pakistan or other countries. Keywords: Human factor, Cyber Security, Perceived Vulnerability, Perceived Benefits